2011
DOI: 10.1007/s11218-011-9155-1
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic motivation, extrinsic motivation, and academic achievement among Indian adolescents in Canada and India

Abstract: The purpose of the present study was to examine the relationships among intrinsic motivation, extrinsic motivation, and academic achievement for the Indian immigrant adolescents in Canada in comparison to their counterparts in India. Descriptive discriminant analysis indicated that the Indian immigrant adolescents in Canada had higher intrinsic motivation and academic achievement than their peers in India. By contrast, the Indian adolescents in India had higher extrinsic motivation than their counterparts in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
2
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 57 publications
(59 reference statements)
7
44
2
7
Order By: Relevance
“…This finding is consistent with theoretical base of the SDT, which proposes that students' fulfillment of basic psychological needs in the classroom, facilitates their self-regulation for learning, academic performance and well being [3]. [8,9,10,12]. Based on the selfdetermination theory, fulfillment of basic psychological needs is influenced by the person's life environment, as well as his personality traits [29].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with theoretical base of the SDT, which proposes that students' fulfillment of basic psychological needs in the classroom, facilitates their self-regulation for learning, academic performance and well being [3]. [8,9,10,12]. Based on the selfdetermination theory, fulfillment of basic psychological needs is influenced by the person's life environment, as well as his personality traits [29].…”
Section: Discussionsupporting
confidence: 82%
“…In fact, obtaining intrinsic motivation in learning and leading learning through internal guides is one of the main purposes of education [3]. Carried out Studies indicate positive relationship between intrinsic motivation and academic achievement [8,9]. Moreover, studies have shown that fulfillment of students' basic psychological needs has positive effect on their academic achievement [10].…”
Section: Self Determination Theorymentioning
confidence: 99%
“…The finding of such a systematic directional prediction from achievement to intrinsic motivation runs in contrast to studies that found a reverse (Areepattamannil et al., ; Gottfried, ; Murayama et al., ; Spinath et al., ) or a reciprocal (Aunola et al., ; Henderlong Corpus et al., ; Luo et al., ; Viljaranta et al., ) pattern. As argued previously, a prominent explanation for this discrepancy is that most previous studies did not use a cross‐lagged design and thus, did not specifically test for reciprocal associations.…”
Section: Discussioncontrasting
confidence: 59%
“…However, the direction of this developmental association remains unclear. Consistent with SDT, some studies have shown that intrinsic motivation predicts achievement and learning behaviors in mathematics (Areepattamannil, Freeman, & Klinger, ; Gottfried, ; Murayama, Pekrun, Lichtenfeld, & vom Hofe, ; Spinath, Spinath, Harlaar, & Plomin, ), but others did not (Bouffard, Marcoux, Vezeau, & Bordeleau, ; Marsh, Trautwein, Lüdtke, Koller, & Baumert, ). A few other studies found that intrinsic motivation and achievement in mathematics are reciprocally related over time (Aunola et al., ; Henderlong Corpus, McClintic‐Gilbert, & Hayenga, ; Koller, Baumert, & Schnabel, ; Luo, Kovas, Haworth, & Plomin, ; Viljaranta et al., ).…”
mentioning
confidence: 88%
“…Educators may use these at a particular time and or in a certain activity. Similarly, the same activity can be seen as intrinsically or extrinsically motivating by different students (Areepattamannil, Freeman, & Klinger, 2011;Butler, 2012;Guay, Chanal, Ratelle, Marsh, Larose, & Boivin, 2010;Pintrich & Schunk, 2002).…”
Section: Motivationmentioning
confidence: 99%